OP36 Evaluating youth mentoring for young people at risk of exclusion from secondary school: results from a feasibility randomised control trial study. (13th September 2016) - Busse, H; Beattie, A; Kipping, R; Gunnell, D; Hickman, M; Macleod, J; Hollingworth, W; Berridge, D; Metcalfe, C; Spiers, S; Campbell, R
Abstract : Background: Youth mentoring is used with vulnerable young people to help improve their health, well-being and educational attainment. While there is growing interest in mentoring programmes among policy makers and practitioners the evidence base is weak with no randomised control trial (RCT) yet undertaken in the UK. The aim of this study was to assess the feasibility and acceptability of conducting a definitive RCT of the effectiveness and cost effectiveness of the Breakthrough Mentoring programme targeted at secondary school students who are at risk of exclusion from school. Methods: Thirty-one young people were approached and twenty-one were recruited to the feasibility study. Participants were aged 12–16 years (mean age = 14.10 years) and randomised to either receive weekly 2-hour mentoring sessions for one academic year (n = 11, intervention) or care as usual (n = 10, control). Participants were asked to complete self-reported questionnaires on a range of measures including the Strength and Difficulties Questionnaire, which were analysed descriptively. Qualitative interviews were conducted with participants and with parents, schools staff, mentors and commissioners as part of the process evaluation. Interviews were facilitated using a topic guide, were audiotaped, transcribed verbatim and analysed thematically. Results: Follow-up at 6 and 12 months was 100% and 86% for 18 months. Participants were happy to complete the self-report questionnaires, showed a good understanding of randomisation and were accepting of this study design. Control group participants reported wanting a mentor and some were mildly upset at not achieving this. Intervention group participants indicated that having an adult mentor, unconnected with the school that they could talk to about their problems helped them to give voice to and deal with difficult feelings. Some mentees reported negative experiences of the way that the mentoring relationship ended. The process evaluation showed that the study design and intervention were acceptable to parents, mentors, schools and commissioners. A need for further evidence on the effectiveness of mentoring was highlighted by commissioners, and parents and schools staff expressed a wish to be informed of progress made by mentees during mentoring sessions. Conclusion: It is feasible and acceptable to recruit, randomise and retain students at risk of exclusion from school to an RCT for 6, 12 and 18 month follow-up. Further research is required to characterise youth mentoring in schools in the UK and to investigate how to best measure its effectiveness before a definitive trial can be considered.